Relentless pursuit : my fight for the victims of Jeffrey Epstein - Edwards, Bradley J.; Henderson, Brittany (Gallery Books, 2020)
The definitive story of the case against Jeffrey Epstein and the corrupt system that supported him told in thrilling detail by the lawyer who has represented Epstein's victims for more than a decade.